Ce qu’observer veut dire - Cyrille Marlin (Projets de Paysage)
The purpose of the article is to focus on the function of the landscape architect in contemporary society to better understand its practical potential. According to how precisely landscape architects consider the choices implied by requests for the observation of landscapes they will define with greater clarity the social function fulfilled by their work and hence the conceptual and practical tools they judge necessary for the performance of this function. Making choices can imply : 1. revisiting the notion of the landscape and disassociating it from any overly explicit aesthetic allusions ; 2. repositioning the practice of the observer landscape architect compared with the more traditional practice of the landscape architect and the practices of the social sciences such as geography, anthropology and sociology, with which it shares many of the same tools and raises the same questions without necessarily resorting to the same methods. To be able to read this article properly, it is necessary to set aside theoretical approaches which have already revealed the existence of some variations in landscaping practices such as landscape designer, landscape developer, landscape mediator, landscape planner, and landscape gardener. The goal is to pave the way for a new approach providing other practical and theoretical perspectives to which some practitioners may be able to relate.